2021
DOI: 10.2147/dmso.s333431
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated lncRNA HCG18 in Patients with Non-Alcoholic Fatty Liver Disease and Its Regulatory Effect on Insulin Resistance

Abstract: Purpose Non-alcoholic fatty liver disease (NAFLD) is a disease associated with genetic-environmental-metabolic stress, which severely damages the liver function of patients. This study aimed to explore the significance and probable functions of HCG18 in NAFLD. Patients and Methods The expression of HCG18 and miR-197-3p was tested by qRT-PCR. The clinical signification of HCG18 was provided by the ROC curve and Pearson correlation. The corresponding mechanism was punctua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Zhang et al reported that increased serum PVT1 has good predictive value for distinguishing NAFLD patients from healthy individuals, with an AUC of 0.895, a sensitivity of 84.0%, and a specificity of 84.6% [ 25 ]. Another lncRNA, HCG18, was identified as a promising candidate biomarker in differentiating NAFLD patients from healthy individuals (AUC = 0.934, sensitivity: 82.8%, and specificity: 89.1%) [ 35 ]. Furthermore, three other studies collectively focused on lncRNA MEG3 expression in NAFLD.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al reported that increased serum PVT1 has good predictive value for distinguishing NAFLD patients from healthy individuals, with an AUC of 0.895, a sensitivity of 84.0%, and a specificity of 84.6% [ 25 ]. Another lncRNA, HCG18, was identified as a promising candidate biomarker in differentiating NAFLD patients from healthy individuals (AUC = 0.934, sensitivity: 82.8%, and specificity: 89.1%) [ 35 ]. Furthermore, three other studies collectively focused on lncRNA MEG3 expression in NAFLD.…”
Section: Resultsmentioning
confidence: 99%
“…Abdulle et al also demonstrated the significance of MALAT1 as a target in diabetic-related diseases 40 . Additionally, HCG18 and BPLN3P are upregulated, which increases the risk of insulin resistance and type 1 diabetes, respectively 41 , 42 . The remaining obtained lncRNAs are novel in this cross-talk which are proposed in this study for future experimental analysis.…”
Section: Resultsmentioning
confidence: 99%
“…From our interaction network, we found that circ_0000946 may have an interaction relationship with miR-412-3p, miR-197-3p, miR-26b-5p, miR-26a-5p, miR-3432-5p, miR-16b-3p, miR-34c -3p and miR-34b-3p. Among them, miR-197-3p [ 48 ], miR-26b-5p [ 49 ] and miR-26a-5p [ 50 ] have showed their correlation with adipocyte differentiation. For circ_0005870, we found it can have an interaction with miR-1249, miR-532-3p, miR-487a-5p, miR-140-3p, miR-216b, miR-423-5p, miR-502a, miR-500-3p, miR-504, miR-128-5p, miR-671-5p and miR-2331.…”
Section: Discussionmentioning
confidence: 99%